Methods Used in Lesson Processes in Primary Grades (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It is up to the teacher and the student to choose the technology to achieve the goal, because the main goal of both parties is to achieve a specific result, and the technology used depends on the level of knowledge of the students, the nature of the group, and the setting.